Method for preparing mechanical luminescent material through laser hot working

Mechatronic materials are prepared by laser thermal processing technology under local high temperature and thermal stress, which solves the problems of grain coarsening and dopant migration in traditional high temperature solid-state methods. This achieves efficient and low-consumption material preparation, improves luminescence performance and application scenarios, and meets the needs of intelligent sensing and biomedical imaging.

CN121293972APending Publication Date: 2026-01-09DONGGUAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511286560.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-10
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

Traditional high-temperature solid-state sintering methods for preparing mechanoluminescent materials suffer from problems such as grain coarsening, phase separation, and luminous efficiency decay. Furthermore, dopants are prone to ion migration at high temperatures, resulting in poor material stability and making it difficult to meet the application requirements of fields such as intelligent sensing and biomedical imaging.

Method used

Laser thermal processing technology is used to achieve in-situ crystallization of raw materials under local high temperature and thermal stress, and to prepare mechanoluminescent materials such as Mn-doped ZnS, CaZnOS and ZnS-CaZnOS. Laser thermal processing technology can shorten the preparation time, reduce energy consumption, and achieve pattern customization and precise control of microstructure.

Benefits of technology

It significantly shortens the preparation time from several hours to several minutes, reduces energy consumption, improves the force-light response sensitivity of the material, broadens the application scenarios, reduces the preparation cost, and improves the luminescence performance and structural accuracy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121293972A_ABST
    Figure CN121293972A_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing a mechanical luminescent material by laser thermal processing, which comprises the following steps: preparing raw materials, weighing the raw materials required by the mechanical luminescent material according to a ratio, transferring the raw materials into an agate mortar, adding absolute ethyl alcohol, grinding for 30 minutes until the raw materials are uniformly mixed, then putting the raw materials into a drying oven, and drying at 60 DEG C for 4 hours; laser thermal processing: uniformly coating the dried raw materials on quartz-loaded glass by adopting a blade coating method, placing the quartz glass under a COlaser emitter, controlling a scanning path, and carrying out laser thermal processing in air to realize in-situ preparation of the laser-induced illuminant; after laser processing is completed, an ear washing bulb is used for purging the surface of a sample, unreacted loose raw materials are removed, the unreacted loose raw materials are taken out through tweezers, and the laser-induced mechanoluminescent material is obtained. Compared with a traditional high-temperature solid-phase method, the preparation time is shortened to several minutes from 5 hours or above, energy consumption is remarkably reduced, and the cost is reduced. And meanwhile, pattern customization and precise regulation and control of an existing microstructure are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of mechanoluminescent materials, and more particularly to a method for preparing mechanoluminescent materials by laser thermal processing. Background Technology

[0002] Mechatronic (ML) materials, with their unique force-light coupling properties, can convert mechanical energy into visible light signals in real time, showing significant application potential in fields such as impact detection and structural health monitoring. Since their discovery at the end of the 20th century, ML materials have gradually expanded from single inorganic crystals to organic molecules, rare earth doped and transition metal composite systems. Their emission bands cover the full spectrum from ultraviolet to near-infrared, and their response time and spatial resolution surpass those of traditional electrical sensors. Their application scenarios have also extended from traditional fields to cutting-edge areas such as intelligent sensing and biomedical imaging.

[0003] In early studies, high-temperature solid-state sintering (HTSS) was the most mainstream preparation technique: ML precursors (such as activators and matrix materials) are thoroughly mixed and sintered at temperatures above 1000°C for an extended period, followed by natural cooling to form dense crystals. While this method offers advantages such as strong atmosphere control and suitability for large-scale preparation, the prolonged high-temperature environment leads to grain coarsening and phase separation, significantly reducing luminescence efficiency. Furthermore, dopants with poor thermal stability (such as rare-earth ions) are prone to ion migration at high temperatures, disrupting the stability of the luminescent centers. Summary of the Invention

[0004] The purpose of this invention is to provide a method for preparing mechanoluminescent materials by laser thermal processing. Using laser thermal processing technology, in-situ crystallization of raw materials is achieved under localized high temperature and thermal stress, forming mechanoluminescent materials such as Mn-doped ZnS, CaZnOS, and ZnS-CaZnOS. Compared with the traditional high-temperature solid-state method, the preparation time is shortened from more than 5 hours to several minutes, and energy consumption is significantly reduced. Simultaneously, the customizable patterns and precise control of the microstructure effectively improve the material's force-light response sensitivity, broaden application scenarios, and reduce preparation costs.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: a method for preparing mechanoluminescent materials by laser thermal processing, comprising the following steps: Step 1: Raw material preparation. Weigh the raw materials required for the mechanoluminescent material according to the specified ratio. Then transfer the raw materials to an agate mortar, add anhydrous ethanol, grind for 30 minutes until evenly mixed, and then place in an oven to dry at 60°C for 4 hours. Step 2, Laser thermal processing: The raw material dried in Step 1 is uniformly coated onto the quartz glass using a blade coating method. The quartz glass is then placed under a CO2 laser emitter, and the scanning path is controlled to perform laser thermal processing in the air, thereby achieving in-situ preparation of the laser-induced luminescent body. Step 3, Post-processing: After laser processing, the sample surface is purged with a rubber bulb to remove unreacted loose material, and then removed with tweezers to obtain the laser-induced mechanoluminescent material.

[0006] Preferably, the raw materials in step one are ZnS and MnCO3, with a molar ratio of 99%:1%.

[0007] Preferably, the raw materials in step one are ZnS, CaCO3 and MnCO3, with a molar ratio of 99%:1%:1%.

[0008] Preferably, the raw materials in step one are ZnS, CaCO3 and MnCO3, with a molar ratio of 3:2:2%.

[0009] Preferably, the laser focal length is fixed at 8mm during the laser thermal processing in step two.

[0010] Preferably, in step two, the laser power ranges from 10 to 50 W, and the scanning speed is from 0.4 to 1.2 cm / s.

[0011] The technical effects of this invention are as follows: 1. The preparation time is shortened from more than 5 hours in the traditional high temperature solid phase method to a few minutes, and the energy consumption is significantly reduced.

[0012] 2. Precise control of microstructure: By utilizing the local high temperature and rapid cooling characteristics of laser, crystallinity, grain boundaries and surface morphology can be controlled to form a ginger-like three-dimensional porous structure or heterojunction, thereby improving the force-optical coupling efficiency.

[0013] 3. Optimized luminescence performance: The fluorescence lifetime of laser-prepared samples is shortened by 41.6% compared to traditional methods (e.g., ZnS-CaZnOS:Mn). 2+ The material's luminescence response speed was reduced from 727.3 ns to 424.9 ns, and the luminescence intensity under mechanical stimulation showed a high linear correlation with the impact force (slope 1.11).

[0014] 4. Functional expandability: Patterned fabrication capabilities meet the spatial resolution requirements of intelligent sensing, and composite materials enable visualized detection of stress propagation. Attached Figure Description

[0015] Figure 1 This is a flowchart of laser fabrication process.

[0016] Figure 2 To prepare sample morphology images.

[0017] Figure 3 Scanning electron microscope image of a sample prepared for laser thermal processing.

[0018] Figure 4 Energy dispersive X-ray image of a sample prepared for laser thermal processing.

[0019] Figure 5 X-ray diffraction and photoluminescence characterization of samples prepared by laser thermal processing and samples sintered at high temperature. Detailed Implementation

[0020] To enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be described in detail below with reference to the accompanying drawings. The description in this part is only exemplary and explanatory, and should not be used to limit the scope of protection of the present invention in any way. Example

[0021] A method for preparing mechanoluminescent materials by laser thermal processing includes the following steps: Step 1: Raw material preparation. Weigh ZnS and MnCO3 in a molar ratio of 99%:1%. Then transfer the raw materials to an agate mortar, add anhydrous ethanol, grind for 30 minutes until they are evenly mixed, and then place them in an oven to dry at 60°C for 4 hours. Step 2, Laser thermal processing: The raw material dried in Step 1 is uniformly coated onto the quartz glass using a blade coating method. The quartz glass is placed under a CO2 laser emitter with a fixed laser focal length of 8mm and a scanning speed of 0.4~1.2cm / s to control the scanning path. Laser thermal processing is carried out in air to achieve in-situ preparation of the laser-induced luminescent body. Step 3, Post-processing: After laser processing, the sample surface is purged with a rubber bulb to remove unreacted loose material, and then removed with tweezers to obtain the laser-induced mechanoluminescent material. Example

[0022] A method for preparing mechanoluminescent materials by laser thermal processing includes the following steps: Step 1: Raw material preparation. Weigh ZnS, CaCO3 and MnCO3 in a molar ratio of 99%:1%:1%. Then transfer the raw materials to an agate mortar, add anhydrous ethanol, grind for 30 minutes until they are evenly mixed, and then place them in an oven to dry at 60°C for 4 hours. Step 2, Laser thermal processing: The raw material dried in Step 1 is uniformly coated onto the quartz glass using a blade coating method. The quartz glass is placed under a CO2 laser emitter with a fixed laser focal length of 8mm and a scanning speed of 0.4~1.2cm / s to control the scanning path. Laser thermal processing is carried out in air to achieve in-situ preparation of the laser-induced luminescent body. Step 3, Post-processing: After laser processing, the sample surface is purged with a rubber bulb to remove unreacted loose material, and then removed with tweezers to obtain the laser-induced mechanoluminescent material. Example

[0023] A method for preparing mechanoluminescent materials by laser thermal processing includes the following steps: Step 1: Raw material preparation. Weigh ZnS, CaCO3 and MnCO3 in a molar ratio of 3:2:2%. Then transfer the raw materials to an agate mortar, add anhydrous ethanol, grind for 30 minutes until they are evenly mixed, and then place them in an oven to dry at 60°C for 4 hours. Step 2, Laser thermal processing: The raw material dried in Step 1 is uniformly coated onto the quartz glass using a blade coating method. The quartz glass is placed under a CO2 laser emitter with a fixed laser focal length of 8mm and a scanning speed of 0.4~1.2cm / s to control the scanning path. Laser thermal processing is carried out in air to achieve in-situ preparation of the laser-induced luminescent body. Step 3, Post-processing: After laser processing, the sample surface is purged with a rubber bulb to remove unreacted loose material, and then removed with tweezers to obtain the laser-induced mechanoluminescent material.

[0024] The comparative example corresponding to the above embodiment differs in step two, which is as follows: High-Temperature Solid State Method (HTSS): The dried raw material is placed in a crucible and then placed in a tube furnace (GSL-1400X, Hefei Kejing Materials Technology Co., Ltd.). The temperature is raised to 1050°C at a heating rate of 10°C / min under an Ar2 atmosphere. After high-temperature calcination for 4 hours, the material is naturally cooled to obtain ML crystals.

[0025] In the actual operation of Examples 1-3, the laser power ranged from 10 to 50 W. When the laser power was 10 to 20 W, a mechanoluminescent material with a needle-like porous structure was prepared. When the laser power was 30 to 40 W, the porous structure on the material surface became irregular due to local melting, specifically as follows: Figure 2 As shown.

[0026] Under fixed-point laser irradiation, when the laser power is only 10 W, the local maximum temperature on the substrate surface can reach 1840 K. Given that CaZnOS crystals can undergo a phase transition at 1100 °C, theoretically, a laser power of P=10 W is sufficient to drive the crystallization transformation of the precursor powder and form ML crystals (related XRD characterization results are shown in [reference]). Figure 5(b) However, the temperature drops rapidly with increasing distance from the laser center: for example, at a distance of only 1 cm from the center, the temperature has already dropped to approximately 470 K, far from sufficient to promote the formation of laser-induced light-emitting diodes (LILs). This significant local temperature rise not only verifies the feasibility of achieving efficient crystallization through laser thermal treatment (LTP) but also indicates its broad application potential in LIL pattern design. To further investigate the effect of laser power on temperature distribution, the surface temperature distribution along the central axis was simulated under different powers. The results show that with increasing laser power, the local maximum temperature increases significantly: for example, when P = 50 W, the local maximum temperature can reach 3700 K. This result further demonstrates that the LTP process can achieve precise control of local temperature by adjusting the laser power, thereby meeting the heat treatment requirements of different ML precursor materials.

[0027] As shown in Figure 2, the ZnS_CaZnOS:Mn (ZCM@LIL) system prepared by the LTP process appears yellow under sunlight, but exhibits a distinct orange photoluminescence phenomenon after excitation by ultraviolet light (UV-256 nm). The uneven shadowed areas on its surface visually reflect the visible porous morphology. Further morphological characterization using scanning electron microscopy (SEM) confirmed that the "pores" formed by CO2 release promoted the spatial connection of the porous rough morphology, forming a porous structure. Specifically, magnified SEM images show that when the laser scanning power P=20 W (Figure 3), the microstructure surface exhibits a hierarchical needle-like porous structure; when the power increases to 30 W, the needle-like structure undergoes local melting, and the porous structure becomes irregular; when the power further increases to 40 W, the melting phenomenon is significantly intensified, the crystal surface tends to be smooth, and the porous structure is greatly reduced. This phenomenon is jointly regulated by the maximum temperature and thermal stress. Furthermore, as shown in Figure 3, with the increase of laser scanning power, the porosity of the ZCM@LIL system gradually decreases due to the intensified microscale melting. To fully demonstrate the porous structural characteristics of the ZCM system, Figure 4 Energy dispersive X-ray spectroscopy (EDS) distributions of Ca, Zn, O, S, and Mn on the surface are presented. Due to the low content of the dopant element Mn, it is difficult to achieve uniform distribution in areas with significant surface undulations, further verifying the successful preparation of the ZCM@LIL system and its elemental distribution characteristics.

[0028] To verify the consistency of phase composition, Figures 5a–c show the XRD characterization results of ZnS:Mn, CaZnOS:Mn, and ZCM systems prepared by LTP and HTSS processes, respectively. For ZnS:Mn, the XRD characteristic peaks of LILs prepared by different laser powers (10–40 W) highly match those of hexagonal ZnS (wurtzite structure, PDF#36-1450) and show significant differences from those of cubic ZnS (zincblende structure, PDF#05-0566). It is known that the phase transition temperature of ZnS from zincblende to wurtzite is approximately 1020 °C, and the wurtzite phase is a more ideal crystalline phase in ML materials due to its excellent structural stability and luminescent properties. XRD analysis results indicate that although the processing time of the LTP process is relatively short, the local high temperature is sufficient to raise the system temperature above 1020 °C, thereby promoting the transformation of the ML precursor into the thermodynamically more stable wurtzite phase ZnS. However, since LILs need to be sampled from the precursor powder after formation, a small amount of unreacted precursor powder may remain in the final XRD sample—for example, trace characteristic peaks of MnCO3 can still be observed at 2θ=31.59°, 34.39° and 36.01°.

[0029] Similarly, for CaZnOS:Mn, the XRD peaks of LILs prepared with different powers are consistent with hexagonal CaZnOS (PDF#01-076-3819), with trace characteristic peaks of CaO observed at 2θ = 32.20°, 37.36°, and 53.86°. This is because CaZnOS may undergo reverse decomposition to generate ZnS and CaO when the synthesis temperature exceeds 1370 K. Furthermore, trace characteristic peaks of CaCO3 (PDF#00-005-0586) are also detected at 2θ = 23.02° and 29.40°, attributed to precursor residues. Finally, for ZCM, except for the trace characteristic peak of CaCO3, the XRD peak positions of LILs prepared with different laser powers are consistent with the HTSS sample, indicating the formation of wurtzite ZnS and hexagonal CaZnOS.

[0030] In summary, the XRD analysis results show that although the XRD diffraction peak intensities of the LIL sample are generally lower than those of the HTSS sample in the three systems, the LTP process can successfully synthesize the target crystalline phase, laying the foundation for further in-depth research on its structure-property relationship.

[0031] In addition, photoluminescence (PL) tests were performed on the three samples prepared by LTP and HTSS, as shown in Figure 5d. The photoluminescence excitation (PLE) test was performed with a fixed detection emission wavelength of 585 nm. The results showed that the PLE peak positions of ZnS:Mn under LTP and HTSS conditions were very similar between 346.3 nm and 347.8 nm. However, for the CaZnOS:Mn and ZCM systems, there was a deviation of about 10 nm in the PLE peak positions of the samples prepared by LTP and HTSS: specifically, the peak positions of CaZnOS:Mn were 340.2 nm (LTP) and 351.5 nm (HTSS), while the peak positions of ZCM were 342.2 nm (LTP) and 352.1 nm (HTSS).

[0032] On the other hand, when the emission wavelength is fixed at 342 nm (Figure 5e), the emission peak positions of ZnS:Mn@LIL and ZnS:Mn@HTSS are still similar, at 588.5 nm and 591.0 nm, respectively, indicating that the luminescence performance of the ZnS:Mn system remains highly consistent under different preparation methods. However, in the CaZnOS:Mn and ZCM systems, the emission peak positions of LTP and HTSS samples still show some deviation, which corresponds to the PLE test results and further demonstrates the influence of different preparation processes on the microenvironment of the luminescent center and the energy transfer process.

[0033] exist Figure 5 The logarithmic PL decay curves for all samples were plotted in f. By fitting the decay curves to a double exponential decay curve, the calculated fluorescence lifetimes provided important evidence for luminescence dynamics studies. Notably, the lifetimes of all three LIL samples were shorter than their corresponding HTSS-prepared samples, with the ZCM system showing the most significant difference—the fluorescence lifetime decreased significantly from 727.3 ns in the HTSS system to 424.9 ns in the LIL system (i.e., a reduction of 41.6%). Lower fluorescence lifetimes are generally associated with higher nonradiative transition probabilities, stronger lattice defects, or faster energy transfer processes, indicating that LILs have faster response speeds and higher dynamic luminescence performance, offering potential advantages for their applications in high-performance sensing and dynamic displays.

[0034] Based on SEM, XRD and PL analysis results, it was confirmed that the LTP process successfully achieved the crystal synthesis of ZnS:Mn, CaZnOS:Mn and ZCM.

[0035] It should be noted that, in this document, the terms “comprising,” “including,” or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.

[0036] This article uses specific examples to illustrate the principles and implementation methods of the present invention. The above examples are only for the purpose of helping to understand the method and core ideas of the present invention. The above descriptions are only preferred embodiments of the present invention. It should be noted that due to the limitations of textual expression, while there are objectively infinite specific structures, those skilled in the art can make several improvements, modifications, or changes without departing from the principles of the present invention, and can also combine the above technical features in an appropriate manner. These improvements, modifications, changes, or combinations, or the direct application of the inventive concept and technical solution to other situations without modification, should all be considered within the scope of protection of the present invention.

Claims

1. A method for preparing mechanoluminescent materials by laser thermal processing, characterized in that, Includes the following steps: Step 1: Raw material preparation. Weigh the raw materials required for the mechanoluminescent material according to the specified ratio. Then transfer the raw materials to an agate mortar, add anhydrous ethanol, grind for 30 minutes until evenly mixed, and then place in an oven to dry at 60°C for 4 hours. Step 2, Laser thermal processing: The raw material dried in Step 1 is uniformly coated onto the quartz glass using a blade coating method. The quartz glass is then placed under a CO2 laser emitter, and the scanning path is controlled to perform laser thermal processing in the air, thereby achieving in-situ preparation of the laser-induced luminescent body. Step 3, Post-processing: After laser processing, the sample surface is purged with a rubber bulb to remove unreacted loose material, and then removed with tweezers to obtain the laser-induced mechanoluminescent material.

2. The method for preparing mechanoluminescent materials by laser thermal processing according to claim 1, characterized in that, The raw materials in step one are ZnS and MnCO3, with a molar ratio of 99%:1%.

3. The method for preparing mechanoluminescent materials by laser thermal processing according to claim 1, characterized in that, The raw materials in step one are ZnS, CaCO3 and MnCO3, with a molar ratio of 99%:1%:1%.

4. The method for preparing mechanoluminescent materials by laser thermal processing according to claim 1, characterized in that, The raw materials in step one are ZnS, CaCO3 and MnCO3, with a molar ratio of 3:2:2%.

5. The method for preparing mechanoluminescent materials by laser thermal processing according to claim 1, characterized in that, In step two, the laser focal length is fixed at 8mm during the laser thermal processing.

6. The method for preparing mechanoluminescent materials by laser thermal processing according to claim 1, characterized in that, In step two, the laser power ranges from 10 to 50W, and the scanning speed is from 0.4 to 1.2 cm / s.